Organ Weights in Relation to Age and Sex in Cynomolgus Monkeys (Macaca fascicularis). (July 2022) - Amato, Rachel; Gardin, Jean F.; Tooze, Janet A.; Cline, J. Mark
Laboratory animal research is an important contributor to both human and animal medicine. Currently, there is extensive use of cynomolgus monkeys ( Macaca fascicularis ) in pathology and toxicology research. The purpose of this study was to define reference values for absolute and percentage organ weights in M fascicularis of different ages and sex. Organ weights were obtained from necropsies of 1022 cynomolgus monkeys at the Wake Forest School of Medicine from 1997 to 2018. Distributions of absolute and percentage weights for each organ were described; sex and age groups were compared using analysis of variance. Age effects on percentage of body weights for each organ were analyzed within each sex. Diet effects were also analyzed. This evaluation showed that male body weights and absolute organ weights were greater for all age groups; however, female organ to body weight percentages were greater for most organs. Percentage of organ weight to body weight declined for the adrenals, brain, lung, thyroid and thymus during maturation, whereas percentage weight of pancreas, prostate, testes, and uterus increased. Animals consuming a high-fat, Western-type diet had a lower body weight than animals consuming a carbohydrate-rich chow diet. This information will be useful for further toxicology and pathology studies concerning cynomolgus monkeys.